2013
DOI: 10.4315/0362-028x.jfp-13-183
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Susceptibility of Planktonic and Attached Cells of Foodborne Pathogens to Bacteriophage P22-Mediated Salmonella Lysates

Abstract: This study was designed to evaluate the lytic activity of bacteriophage P22 against Salmonella Typhimurium ATCC 19585 (Salmonella Typhimurium P22(-)) at various multiplicities of infections (MOIs), the susceptibility of preattached Salmonella cells against bacteriophage P22, and the effect of P22-mediated bacterial lysates (extracellular DNA) on the attachment ability of Listeria monocytogenes ATCC 7644 and enterohemorrhagic Escherichia coli ATCC 700927 to surfaces. The numbers of attached Salmonella Typhimuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Bacteria biofilms are highly resistant to antibiotics because of structural rigidity and reduced metabolic activity, which can cause serious persistent and chronic infections (16). Previous study reported that the bacterial cell components, including extracellular DNA, can promote biofilm formation (17). In this study, the phage-induced bacterial lysates, however, did not have a great influence on the induction of biofilm formation by S. aureus in combination.…”
Section: Resultsmentioning
confidence: 54%
“…Bacteria biofilms are highly resistant to antibiotics because of structural rigidity and reduced metabolic activity, which can cause serious persistent and chronic infections (16). Previous study reported that the bacterial cell components, including extracellular DNA, can promote biofilm formation (17). In this study, the phage-induced bacterial lysates, however, did not have a great influence on the induction of biofilm formation by S. aureus in combination.…”
Section: Resultsmentioning
confidence: 54%
“…Above all, phages only infect bacteria and are not harmful to humans, making them safe for application in the clinic and food products ( 24 ). A recent study found that phages have high efficiency in reducing and controlling bacterial biofilms on various surfaces, such as those produced by Pseudomanas aeruginosa, Salmonella, E. coli , and Listeria monocytogenes ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phages only infect bacteria and are not harmful to humans, making them a safe application in clinical and food products [25]. A recent study found that phages are highly effective at reducing and controlling bacterial biofilms on various surfaces formed by species such as Escherichia coli, Salmonella sp., Pseudomonas aeruginosa, and Listeria monocytogenes [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%